Personalized Oral Health Care From Concept Design to Clinical Practice - Polverini, Peter J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides an overview of the evolving oral health care environment and describes an array of technologies, under development or already applied in practice, that are impacting on risk assessment, diagnosis, and therapy. Detailed consideration is also devoted to personalized health insurance in the new environment, the impact of personalized health care on the economics of health care, and the consequences for the global diagnostic market place and improved access to care. The changes in dental education required to produce dentists better equipped to participate in the new health care environment are examined, and the book concludes by considering key opportunities and challenges.
Emerging Role of Personalized Medicine in Oral Health: Personalized Oral Health Care and the New Health Care Environment -- Omics Technology: Application to Oral Disease Prevention, Disease Prediction and Diagnosis -- Omics-Based Technology Development -- Personalized Medicine in Dental Practice: Personalized Oral Medicine and Transformation of Dental Practice -- Health Information Technology and Integrative Medicine -- Comprehensive Genetic Testing in Dental Practice -- Biomarkers for Individualized Oral Cancer Therapy -- Metabolomics and Oral Disease Diagnosis -- Companion Diagnostics in the Dental Office -- Genomics of Dental Caries and Caries Risk Assessment -- Genomics of Periodontal Risk Assessment and Disease Progression -- Personalized Oral Medicine and Public Health: Personalized Oral Medicine and Personalized Health Insurance -- The Economics of Personalized Oral Medicine -- Educating Dental Students and Dental Practitioners for the Practice of Personalized Oral Medicine -- Personalized Oral Health Care and the Future Oral Health Care Workforce -- Personalized Oral Medicine and the Global Diagnostic Market Place -- Opportunities and Challenges Shaping the Future of Personalized Oral Health Care.
Keywords: Dentistry; Oral surgery; Maxillofacial surgery; Dentistry; Oral and Maxillofacial Surgery